Relationships between dimensions of emotional experience, rumination, and nonsuicidal self-injury: An application of the Emotional Cascade Model - Hatzopoulos, Katerina; Boyes, Mark; Hasking, Penelope (WILEY, 2022)
Objective: The Emotional Cascade Model posits that nonsuicidal self-injury (NSSI) functions to distract from cascades of intense negative emotion and rumination. We investigated the moderating role of rumination in the relationships between reactivity, intensity, and perseveration of emotion and NSSI. Method: University students (N = 992) completed self-report measures of self-injury, emotional reactivity, intensity and perseveration, and rumination. Results: Together, the dimensions of negative emotion were associated with NSSI, but none contributed unique variance. For positive emotion, reactivity was negatively associated with history of self-injury and perseveration was negatively associated with frequency of the behaviour. Rumination was associated with NSSI, but did not moderate associations between the dimensions of negative emotion and self-injury. Rumination moderated the relationship between perseveration of positive emotion and history of NSSI, such that it was only significant at high levels of rumination. Conclusion: Findings highlight the importance of dimensions of positive emotion in understanding self-injury.